Acoustical physical constants around room temperature for Ca3TaGa1.5Al1.5Si2O14 single crystal. Issue 24 (1st November 2015) - Ohashi, Y.; Kudo, T.; Yokota, Y.; Shoji, Y.; Kurosawa, S.; Kamada, K.; Yoshikawa, A.
Abstract : A full set of acoustical physical constants was determined for Ca3 TaGa1.5 Al1.5 Si2 O14 (CTGAS) single crystal from bulk wave velocities measured by the ultrasonic micro‐spectroscopy method. Several plate specimens were cut perpendicular to the X ‐, Y ‐, Z ‐, 35.25° Y ‐, and 139.74° Y ‐directions from a CTGAS single crystal ingot grown by Czochralski technique. Following measurements of dielectric constants and density, elastic constants, piezoelectric constants, and their temperature coefficients were determined from longitudinal wave and shear wave velocities measured for the CTGAS specimens at around room temperature. It was demonstrated that the as found constants could provide calculation accuracy within ±0.15% in leaky surface acoustic wave velocity. The determined constants were used for numerical calculation of the cut angle, at which the temperature coefficient of shear wave velocity becomes zero. This angle corresponded to 147.9° Y ‐cut substrate that had electromechanical coupling factor of k 2 = 3.2%. This parameter is about four times greater than that of AT‐cut α‐quartz.